Pengurangan Penggunaan Pupuk Urea Melalui Pemanfaatan Tanaman Turi Mini (Sesbania rostrata) pada Budidaya Jagung Manis - Iqbal Effendy; Paiman Paiman; Neni Marlina (Vegetalika, 2020)
The use of inorganic fertilizer in agriculture as well as on sweet corn cultivation is quite high. Inorganic fertilizer recommended for sweet corn is  35 kg urea ha-1, 150 kg TSP  ha-1 and 150 kg KCl ha-1. Besides high prices, its difficult to find when needed. To overcome this, an experiment was carried out by utilizing TM plants for reducing urea input. This research was carried out in Air Kuti Village, South Lubuklinggau District I, Lubuklinggau City, South Sumatera Province with an altitude of 110 meters above sea level (ASL), from April to June 2017. The experiment was arranged out in a randomized completely block design (RCBD) factorial 4 x 3 and repeated three times. The first factor was treatment combination of inorganic N fertilizer (urea) and TM plants consisted 4 kinds i.e: 75% urea and 1 TM plant, 50% urea and 2 TM plants, 25% urea and 3 TM plants, and 0% urea and 4 TM plants. The second factor was a frequency of urea application consisted of 3 levels i.e: 1-time application 15 days after planted (15 DAP), 2 times application (15 and 30 DAP), and 3 times application (15, 30 and 45 DAP). The results showed that application of urea fertilizer dosage of 25% recommended (108,75 kg urea ha-1) combinated with 3 stem of TM plants produced the best growth and yield of sweet corn. The frequency of urea application 3 times produced the best growth and yield of sweet corn.